(untitled) (Bangladesh Journal of Child Health, 2022)
Background: Septicemia is the commonest cause of neonatal mortality and severe morbidity. Positive bacterial blood culture result confirms clinically suspected sepsis but it is too late to start antibiotic. We need a easy, reliable and cost effective test to diagnose sepsis in time. Objective: To see the relation of toxic granule and immature neutrophil with neonatal sepsis. Material & Methods: This hospital based, cross-sectional study was conducted on 152 neonate with suspected sepsis admitted in Dhaka Shishu Hospital during January 2013 to April 2014. After enrollment all studied neonate were investigated with complete blood cell count, CRP and Blood culture before starting treatment with antibiotic. Raised immature to total neutrophil ratio >0.2 and toxic granules in neutrophil were correlated with positive blood culture test using x2 test. Result: Out of 152 studied neonate 61.89% were male, 41.94% premature, 48.85% low weight. Blood culture result was found positive in 7.24% neonate. Leukopenia (WBC<5000/mm3), Neutropenia (Neutrophil <1750/mm3), Immature to total neutrophil ratio (I:T) >0.2 and toxic granules were present significantly in sepsis. The sensitivity and specificity of toxic granules to diagnose neonatal sepsis was correspondingly 91.67% and 75% & that of I: T>0.2 were 90.91% and 66.67%. Conclusion: Toxic granules and Immature to total neutrophil ratio (I: T) >0.2 can be considered as useful tools in the diagnosis of neonatal sepsis to start antibiotic earlier, especially where there is limited modern investigation facilities. BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 141-146